Regenerated grating produced in a multimaterial glass-based photosensitive fiber with an ultrahigh thermal regeneration ratio - Yang, Hang Zhou; Paul, Mukul Chandra; Das, Shyamal; Dhar, Anirban; Qiao, Xue Guang; Nazal, Nurul Asha Mohd; Lim, Kok Sing; Ahmad, Harith (Optical Society of America, 2019)
This work demonstrates thermal regeneration of gratings inscribed in a new type of multi-material glass-based photosensitive fiber. And isothermal annealing procedure has been carried out on a type-I seed grating (SG) imprinted in erbium-doped zirconia-yttria-aluminagermanium (Er-ZYAG) silica glass-based fiber, which is initiated from room temperature of 25°C up to 900°C. The findings show that the created regenerated grating (RG) has an ultrahigh thermal regeneration ratio with a value of 0.72. © 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement.